THE IMPACT of GLOBALISATION on EMPLOYMENT STATUTE RELATED to EMPLOYERS in ZIMBABWE - Fore, Cleopas; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2021)
Globalisation led to the reduction of barriers between countries and intensified international interdependency such that developments unfolding in a faraway country now affect the rest of the world in economic, political and social aspects (Giddens, 1990). The Zimbabwean labour market and its national labour legislation have not been spared from the impact of globalisation. Zimbabwean labour legislation had had several amendments from its inception in 1985 to date. The amendments done at each epoch had caused a serious outcry from both labour and business with the main accusations arising from unions who claimed that the effects of globalisation and the government’s desire to lure foreign direct investment (FDI) led to a serious bias towards employers. It is against this background that this article’s objective is to interrogate the impact of globalisation on labour legislation for employers. The article adopted a qualitative paradigm and made use of interviews and participants' memoirs to understand this phenomenon. Results were analysed thematically by use of both Nvivo 10 and manual coding. Results showed that globalisation has an impact on labour legislation for employers. Foreign direct investment and special economic zones were identified as drivers of globalisation responsible for positive impact on labour legislation for employers by influencing deregulation of unfriendly employment laws, instituting flexible contract of employment, easy termination of contracts of employment, and giving immunity from dictates of the labour laws for employers operating in special economic zones. The positives of globalisation for employers resulted in direct negatives for employees. The article recommends that employers need to put into context both globalisation dynamics and dictates of the labour legislation to ensure employee dignity and fair globalisation